The influence of cultural food security on cultural identity and well-being: a qualitative comparison between second-generation American and international students in the United States - Wright, Kathrine E.; Lucero, Julie E.; Ferguson, Jenanne; Granner, Michelle L.; Devereux, Paul G.; Pearson, Jennifer L.; Crosbie, Eric (My University, 2021)
The purpose of this study was to explore the impact of cultural food insecurity on identity and well-being in second-generation American and international university students. Thirty-one semi-structured interviews were conducted from January–April 2020. Audio transcripts were analyzed using continuous and abductive thematic analysis. Students indicated that cultural foodways enhanced their well-being by facilitating their cultural/ethnic identity maintenance, connection, and expression. Conversely, cultural food insecurity diminished student well-being due to reduced cultural anchors, highlighting the importance of cultural food in this population. Universities that reduce cultural foodways barriers may mitigate cultural food insecurity for second-generation American and international university students.
Keywords: food security; culture; identity; well-being; student